Suppression of human T cell proliferation by the caspase inhibitors, z-VAD-FMK and z-IETD-FMK is independent of their caspase inhibition properties - Lawrence, C.P. (Academic Press, 2012)
The caspase inhibitors, benzyloxycarbony (Cbz)-l-Val-Ala-Asp (OMe)-fluoromethylketone (z-VAD-FMK) and benzyloxycarbonyl (Cbz)-Ile-Glu (OMe)-Thr-Asp (OMe)-FMK (z-IETD-FMK) at non-toxic doses were found to be immunosuppressive and inhibit human T cell proliferation induced by mitogens and IL-2 in vitro. Both caspase inhibitors were shown to block NF-κB in activated primary T cells, but have little inhibitory effect on the secretion of IL-2 and IFN-γ during T cell activation. However, the expression of IL-2 receptor α-chain (CD25) in activated T cells was inhibited by both z-VAD-FMK and z-IETD-FMK, whereas the expression of the early activated T cell marker, CD69 was unaffected. During primary T cell activation via the antigen receptor, both caspase-8 and caspase-3 were activated and processed to their respective subunits, but neither caspase inhibitors had any effect on the processing of these two caspases. In sharp contrast both caspase inhibitors readily blocked apoptosis and the activation of caspases during FasL-induced apoptosis in activated primary T cells and Jurkat T cells. Collectively, the results demonstrate that both z-VAD-FMK and z-IETD-FMK are immunosuppressive in vitro and inhibit T cell proliferation without blocking the processing of caspase-8 and caspase-3.